Bibliometric Analysis on Agronomy Topics - Judijanto, Loso; Sarie , Fatma; Safruddin, Safruddin (Westscience Press, 2024)
This study employs bibliometric analysis and network visualization techniques to explore the evolution and current trends in agronomy research over the past decade. Through a series of VOSviewer visualizations, we analyze thematic clusters, research trends over time, author collaborations, and potential research opportunities within the field. Our findings indicate a dynamic shift from foundational topics such as soil and nutrient management towards more complex issues like crop-specific adaptations and environmental stress responses. Additionally, the analysis of co-authorship networks reveals robust collaborative patterns among scholars, emphasizing both dense clusters and isolated research activities. The study also identifies emerging research areas, including sustainable pest management and the agronomic impact on food quality, highlighting gaps and opportunities for future research. This comprehensive overview not only charts the scientific landscape of agronomy but also serves as a guide for future scholarly endeavors aimed at enhancing sustainable agricultural practices.